Overview of a Final Meeting of a Consortium of the ”Europeana Newspapers” Project - Dakić, Nataša; Kavaja Stanišić, Dejana (Infotheca - Journal for Digital Humanities; Vol 15 No 2 (2014): Infotheca - Journal for Digital Humanities, 2024)
The project “Europeana Newspapers” was financed by the European Commission within the CIP ICT-PSP Best Practice Network 5th Call. At first, there were 18 full partner institutions1 , among which there were some of the most important national and university European libraries, including the University Library “Svetozar Marković”. In the meantime, the importance of the project was recognized so it has spread and many libraries, organizations and other European projects have become part of it.